# How do you differentiate #f(x)=xsinx# using the product rule?

##### 2 Answers

Jul 25, 2016

hi

PRODUCT RULE SAYS

if to diffrentiate "uv"( **here i will take w.r.t to x)**

i.e

i.e u must know

diffrentiation of

here..,

**diffrentiation of x=(1)

diffrentiation of" sinx" is "

NOW,

**xcos(x)+sin(x)**

=

So diffrentiation of F(X)=x sin(x)-=x cos(x)+sin(x)

Nov 12, 2017

#### Answer:

#### Explanation:

#"given "f(x)=g(x)h(x)" then"#

#f'(x)=g(x)h'(x)+h(x)g'(x)larrcolor(blue)"product rule"#

#g(x)=xrArrg'(x)=1#

#h(x)=sinxrArrh'(x)=cosx#

#rArrf'(x)=xcosx+sinx#